Entrepreneurship, communication and ICT in secondary education - Medina Vidal, F., (2017)
Education is essential to developing young people’s skills and culture. It is vital that entrepreneurship education is addressed from the secondary education. Entrepreneurship education is essential not only to shape the mindsets of young people but also to provide the skills that are important to developing an entrepreneurial culture. The entrepreneurship key competence refers to an individual’s ability to turn ideas into action. It includes creativity, innovation, and the ability to plan projects in order to achieve objectives. Besides, communication and ICT are relevant in innovation processes in organizations, especially in schools where people interact daily and it is intended to ensure a good future for the organization. In schools, the existence of good communication and the use of ICT is a relevant factor for the integration of teaching innovative projects related to entrepreneurship. A good communication ensures the dissemination of educational innovation processes adopted by the teachers. It´s relevant to improve teaching practice. Communication and the ICT play a key role in the processes of educational innovation. The incorporation of innovative materials, ICT, courses and communication activities, and the use of the media to extract information, are very important. Communication is essential in the secondary education. If the communication flows were eliminated in the school, we would not have school. Communication is introduced into all activities of the school, representing an important tool with which individuals understand their role in the school and integrates organizational departments. The secondary schools are organized through a model based on the participation and collaboration of its component, coordinating the actions of different people in order to achieve the proposed educational objectives. Therefore, the optimal operation of a secondary school is closely related to communication processes taking place in this organization. This paper studies the entrepreneurship, communication processes and the ICT in secondary education. Media and communication channels used in secondary schools to spread the teaching innovation projects related to the entrepreneurship are studied. Supports or conventional tools and new technologies for communication in educational organizations are also analysed when it is studied and worked the entrepreneurship in the classroom.